Metabolic turnover of human c-rasH p21 protein of EJ bladder carcinoma and its normal cellular and viral homologs. - Ulsh, L S (1984)
The EJ bladder carcinoma oncogene is activated by a point mutation in the c-rasH proto-oncogene at the 12th amino acid codon. In an attempt to understand the mechanism of oncogenic activation, a comparative study was undertaken to examine the metabolic turnover and subcellular localization of the p21 protein encoded by the EJ oncogene, the viral oncogene, and its normal cellular homolog. Pulse-labeling experiments indicated that both c-ras p21 proteins were synthesized by a very similar pathway, as was observed for the viral p21 protein of Harvey murine sarcoma virus. The pro-p21 proteins were detected in free cytosol, and the processed products were associated with plasma membrane. The intracellular half-life of p21 proteins was determined by pulse-labeling and chasing in the presence of excess unlabeled methionine. Although both p21 proteins of EJ and the normal c-ras genes which are not phosphorylated have a half-life of 20 h, the viral p21 protein of Harvey murine sarcoma virus which includes a phosphorylated form is much more stable in cells, having a half-life of 42 h, apparently due to phosphorylation.